Intravenous iron therapy for heart failure and iron deficiency: An updated meta‐analysis of randomized clinical trials - Mushood Ahmed (19231379) (2024)
Heart failure (HF) patients frequently exhibit iron deficiency, which is associated with a poor prognosis. Although various trials have been conducted, it is uncertain if intravenous (IV) iron replenishment improves clinical outcomes in HF patients with iron deficiency. A comprehensive literature search was conducted using PubMed/MEDLINE, Embase, and the Cochrane Library from inception till 15 September 2023 to retrieve randomized controlled trials (RCTs) that compared IV iron therapy with placebo or standard of care in patients with HF and iron deficiency. Clinical outcomes were assessed by generating forest plots using the random‐effects model and pooling odds ratios (ORs) or weighted mean differences (WMDs). Fourteen RCTs with 6651 patients were included. IV iron therapy showed a significantly reduced incidence of the composite of first heart failure hospitalization (HHF) or cardiovascular (CV) mortality as compared with the control group (OR = 0.73, 95% CI: 0.58 to 0.92). The IV iron therapy resulted in a trend towards lower CV mortality (OR = 0.88, 95% CI: 0.76 to 1.01), 1‐year all‐cause mortality (OR = 0.85, 95% CI: 0.71 to 1.02), and first HHF (OR = 0.73, 95% CI: 0.51 to 1.05), and an improved left ventricular ejection fraction (LVEF) (MD = 4.54, 95% CI: −0.13 to 9.21). Meta‐regression showed a significant inverse moderating effect of baseline LVEF on the first HHF or CV death. In patients with HF and iron deficiency, IV iron therapy reduced the incidence of composite of first HHF or CV mortality. There was a trend of lower overall CV and 1‐year all‐cause mortality, first HHF, and improved LVEF with IV iron therapy. Other Information Published in: ESC Heart Failure License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ehf2.14905